2009
DOI: 10.1111/j.1533-2500.2009.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Ultrasound and Nerve Stimulation‐Guided Thoracic Epidural Catheter Placement for Analgesia Following Anterior Spine Fusion in Scoliosis

Abstract: Anterior spine fusion by thoracotomy is indicated for the treatment of idiopathic scoliosis. Although epidural (EP) analgesia represents the most effective way to provide adequate analgesia after thoracotomy, scoliosis patients have substantial anatomic variations that make EP catheter placement more difficult and often contraindicated. This case report describes a safe, effective technique for placing a thoracic EP catheter in a young patient undergoing anterior spine fusion surgery by thoracotomy. The proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Despite concerns about feasibility, 16,17 we have shown that preoperative epidural catheter insertion can be performed without raising significant concerns and a high success rate of 96%, corresponding to that reported in the nonscoliotic spine. 18 Obstacles to TEC placement in the scoliotic spine are most often caused by the axial rotation of the vertebral bodies and angulation of the spinal processes.…”
Section: Discussionmentioning
confidence: 67%
“…Despite concerns about feasibility, 16,17 we have shown that preoperative epidural catheter insertion can be performed without raising significant concerns and a high success rate of 96%, corresponding to that reported in the nonscoliotic spine. 18 Obstacles to TEC placement in the scoliotic spine are most often caused by the axial rotation of the vertebral bodies and angulation of the spinal processes.…”
Section: Discussionmentioning
confidence: 67%
“…At the level of the thoracic and cervical spine, visualization of the epidural space is much more difficult than that in the lumbar spine but there are a few studies that have been published about the clinical utility of the ultrasound-guided neuraxial technique [11,21,22]. Correlation was excellent in all studies (Pearson correlation coefficients, 0.80-0.99), whether measurements were made in the sagittal, oblique, or transverse views.…”
Section: Discussionmentioning
confidence: 93%
“…Only three articles pertained to ultrasound imaging of the thoracic spine. 11,16,63 The methodology and results of the RCTs and observational studies are summarized in tables 2 and 3.…”
Section: Literature Search Strategy and Resultsmentioning
confidence: 99%
“…It is only logical that ultrasound would be most helpful in patients with poor or abnormal anatomic landmarks, and this is supported by numerous case reports of successful ultrasound-guided neuraxial block in patients with marked obesity (five reports), 17,20,62,67,75 previous spinal surgery and instrumentation (seven reports), 18,59 -61,65,66,68 and spinal deformity (four reports). 16,32,58,63 In one of the five published RCTs, Grau et al 8 specifically enrolled 72 parturients in whom neuraxial block was anticipated to be difficult because of the presence of spinal deformity, obesity (body mass index more than 33 kg/m 2 ), or a history of previous difficulty. Patients in whom ultrasound imaging was used underwent fewer needle passes (1.5 Ϯ 0.9 vs. 2.6 Ϯ 1.4, P Ͻ 0.001) at fewer spinal interspaces (1.3 Ϯ 0.5 vs. 1.6 Ϯ 0.7, P Ͻ 0.05) than did the control group.…”
Section: Does the Ultrasound-guided Technique Reduce The Technical DImentioning
confidence: 99%